Sprint Hurdling - Thorson, M. (Techniques Magazine, 2019)
The short hurdle races (100m Hurdles for woman and 110m Hurdles for men) are a rhythmic sprint over 10 equally-spaced barriers that require speed, power and technical efficiency. The women´s 100m Hurdle race consists of 10 hurdles set at 33´´ in height. The distance to the first hurdle is 13m and the distance between 8.5m, with a run-in after the last hurdle of 10.5m. The men´s 110m Hurdles consists of 10 hurdles set at 42´´ and the distance to the first hurdle is 13.72m (45 feet). The distance between the hurdles is 9.14m (30 feet), with a run-in distance 14.02m. This article will attempt to provide coaches with a concise, practical, user-friendly guide to training at a higher level and ultimately performing better in the sprint hurdles. Our goal is to present the technical aspects and necessary training in a comprehensive, yet practical application that all coaches and athletes can employ to improve their performances.